Factors Influencing Saudi Nurse Turnover: An Empirical Investigation in Ministry of Health Hospitals in Jeddah City - Alharthi, Raniah. H.; Alzahrani, Norah.A.; Abduljabar, Dalal.F.; Alharbi, Duaa.A.; Magliah, Rawan.J.; Alhatemi, Shekha.A.; Alahmadi, Rawan.H.; Alhuzali, Abdulrahim.M.; Alabdali, Abeer.H.; Alshengiti, Reham.B.; Alotaibi, Abeer.F.; Alsharif, Sarah.K.; et al. (Journal of Posthumanism, 2024)
Health systems worldwide are grappling with an increasing array of challenges on a daily basis. One of the most pressing issues is the growing demand for healthcare services, accompanied by inadequate physical and human resources. Additionally, the global shortage of nursing staff has become a critical concern, driven by various reasons that differ from one country to another. Traditionally, nursing has been viewed as a predominantly female profession, with women making up the majority of the workforce. This research aims to explore the reasons behind nursing turnover in Saudi Arabia and will address issues such as family responsibilities, guardianship decisions, societal perceptions, and demographic influences on nurses’ ability to remain in their profession